Improving Fifth-Grade Students' Learning Motivation Utilizing Discovery Learning Model Assisted by Snakes and Ladders Media - Mayuni, Anju; Masfuah, Siti; Ermawati, Diana (EduBasic Journal: Jurnal Pendidikan Dasar, 2024)
The background of this study is the inadequate motivation of students to engage in the classroom learning process. This study aims to enhance students' motivation to learn mathematics by utilizing the discovery learning model supported by Snakes and Ladders media. This study employed a classroom action research (CAR) methodology at the State Elementary School of Panjang 01, involving 26 students as the subjects of the research. The study was carried out in two cycles, with each cycle comprising two meetings. The techniques utilized for data analysis were both quantitative and qualitative. The techniques employed for data collection included observation, interviews, questionnaires, and documentation. The findings indicated that students' motivation to learn has the potential to improve with each cycle. In Cycle I, the success percentage of learning motivation was recorded at 53.84%, which saw an increase to 92.30% in Cycle II. This study employed group discussions to enhance student engagement and enthusiasm in the learning process. This has the potential to enhance students' motivation to engage in learning. The implementation of the discovery learning model, supported by Snakes and Ladders media, can enhance student engagement and boost motivation in mathematics education. It can be concluded that the implementation of the Snakes and Ladders media-assisted model has the potential to enhance the motivation of fifth-grade students at the State Elementary School of Panjang 01.